Elucidations on botanic knowledge in China during the Qing Dynasty - Métailié, Georges (Circumscribere International Journal for the History of Science, 2012)
Before the first book on modern botany was published in China in 1858, other works on plants were written by Chinese scholars during the 18th and 19th centuries. Two authors are discussed here, Cheng Yaotian (1724-1814) and Wu Qijun (1789-1847). Contrasting with the usually admitted teleological interpretations, I analyzed their work within the framework of the movement of evidence-based research (kaozheng xue), which brings an original approach to the plant universe to light.